Detection of Lectin Clustering in Self‐Assembled, Glycan‐Functionalized Amphiphiles by Aggregation‐Induced Emission Luminophores. Issue 1 (11th November 2022) - Banger, Alexander; Pasch, Peter; Blawitzki, Luca‐Cesare; Weber, Simon; Otten, Marius; Monzel, Cornelia; Schmidt, Stephan; Voskuhl, Jens; Hartmann, Laura
Abstract: Amphiphilic glycan‐functionalized oligomers are derived by solid‐phase polymer synthesis and applied in both, self‐assembled micelles as well as giant unilamellar vesicles, as simplified models of the cell's glycocalyx. Additionally, an aggregation‐induced luminophore is introduced into the amphiphilic glycomacromolecules showing no fluorescence when the molecule is free in solution. Combining glycomacromolecules carrying a binding glycan motif and the luminophore with glycomacromolecules or other amphiphiles with no binding motifs and no luminophore in self‐assembled structures, micelles and vesicles exhibiting no or only very little fluorescence are obtained. Only upon clustering of the binding glycan motifs through interaction with a multivalent lectin receptor, an increase in fluorescence is observed. Thus, clustering events within these self‐assembled structures can be detected and localized. Abstract : Glycan‐functionalized amphiphiles equipped with an AIE‐luminophore are attained via solid‐phase polymer synthesis and assembled into supramolecular assemblies (i.e., micelles and giant unilamellar vesicles). Driven by multivalent lectin‐carbohydrate binding, aggregation‐induced emission is then prompted or enhanced through the formation of local clusters or aggregates.